School Culture-Based Religious Character Education Design at MI Nursyamiyah Plumpang Tuban - Ikmal, Hepi; Sa'adah, Nurul Alfiyatus (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
Religious character is one of the characters that play a significant role in the formation of an individual personality. Religious character education should be given as early as possible so that children can behave following the teachings of Islam. As educational institutions, schools are responsible for material learning and the formation and development of student character. This article describes the school culture-based religious character education design contained in MI Nursyamiyah Plumpang Tuban. This research uses qualitative research with a case study approach. This study resulted in findings that the design of school culture-based religious character education was implemented through compulsory school activities, teacher habituation and example, and school rules. Compulsory school activities include Dhuha and Dzuhur prayers in congregation, Asmaul Husna readings, wirid readings, barzanji readings, and tahlil readings. The habits applied are good habits that students must make, while the teacher's example is given through giving examples by the teacher in speaking and acting following Islamic law. School rules are made by considering Islamic values and norms that apply in society